2009
DOI: 10.1111/j.1462-5822.2008.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenesinduces oncosis in macrophages through the activation of an inflammatory programmed cell death pathway

Abstract: SummaryMacrophages are crucial components of the host defence against Streptococcus pyogenes. Here, we demonstrate the ability of S. pyogenes to kill macrophages through the activation of an inflammatory programmed cell death pathway. Macrophages exposed to S. pyogenes exhibited extensive cytoplasmic vacuolization, cellular and organelle swelling and rupture of the plasma membrane typical of oncosis. The cytotoxic effect of S. pyogenes on macrophages is mediated by the streptococcal cytolysins streptolysin S a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 58 publications
8
95
1
Order By: Relevance
“…The intracellular ATP level of fluopsin C-treated MCF-7 cells at 3 h was depleted to less than 35% of the control, which confirmed that fluopsin C could induce oncosis in MCF-7 cells rather than apoptosis. Several investigators have shown that cells in an aerobic environment are constantly generating ROS [23,24] . Because the physiologic levels of ROS can serve as signaling molecules to regulate transcription, excessive ROS production leads to oxidative stress, damage to intracellular molecules and organelles, and, ultimately, cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular ATP level of fluopsin C-treated MCF-7 cells at 3 h was depleted to less than 35% of the control, which confirmed that fluopsin C could induce oncosis in MCF-7 cells rather than apoptosis. Several investigators have shown that cells in an aerobic environment are constantly generating ROS [23,24] . Because the physiologic levels of ROS can serve as signaling molecules to regulate transcription, excessive ROS production leads to oxidative stress, damage to intracellular molecules and organelles, and, ultimately, cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Fluopsin C induced ATP depletion, ROS generation and Δψ m collapse Several studies have suggested that ROS and cellular ATP play a pivotal role in determining whether cell death is apoptotic or oncotic [2,23,24] . Figure 8A shows that the cellular ATP content of MCF-7 cells in the presence and absence of fluopsin C was significantly decreased.…”
Section: Fluopsin C Destroyed the Cell Skeletonmentioning
confidence: 99%
“…Many bacterial pathogens actively secrete toxins and other soluble factors to aid in the destruction of host tissue, to initiate signaling changes in host cells or to manipulate immune system responses during the course of infection [1][2][3][4][5][6][7][8][9][10] . Though methods have been developed to successfully purify and produce many of these important virulence factors for study, some bacterial products have unique structures or extensive posttranslational modifications that make them recalcitrant candidates for purification methods and thus cannot be studied in isolation using in vitro systems.…”
Section: Introductionmentioning
confidence: 99%
“…This fits with a recent report that showed that GAS can induce mitochondrial permeability leading to bioenergetic and redox damage. Thus evading host immune defense and causing inflammatory programmed cell death in monocytes (Goldmann 2009). Furthermore, it results have been recently reported that GAS streptolysin S and O virulence factors Panel A. Venn diagram of differentially expressed genes in blood of resistant and susceptible strains, showing common (shared) and unique genes.…”
Section: Figure 4-1 Experimental Design To Test Gene Expression Diffmentioning
confidence: 99%
“…Specifically, we wanted to test the hypothesis that effective innate responses in the early stages of infection is directly associated with resolution of GAS infection, and better outcome of GAS sepsis. We based our hypothesis on studies from our group and other groups that showed that neutrophils (Voyich et al, 2004;Buchanan et al, 2006;Nilsson et al, 2006;Soehnlein et al, 2008a;Navarini et al, 2009), macrophages (Goldmann et al, 2004a;Thulin et al, 2006;Goldmann et al, 2009), NK cells (Goldmann et al, 2005b;Takahashi et al, 2007) and dendritic cells (Loof et al, 2008;Cortes and Wessels, 2009;Yong et al, 2009), each play an important role in streptococcal infections according to the site and the stage of infection. We started our cellular dissection by examining the role of neutrophils in differential susceptibility to GAS sepsis.…”
Section: Chapter 5 Analysis Of Cellular Populations Modulating Diffementioning
confidence: 99%